Jamaica. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Jamaica during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as project management, financing, marketing, seeds, agrochemicals, greenhouses, horticulture, nutrition, fodder and good management practices. Finally, it supported the improvement of businesses, hygienic sacrifices, the inclusion of women, the raising of small ruminants, meat production, and the management of disasters, such as hurricanes.